Fostering Quality Education (SDG 4): Transforming QR Codes from 'Scanning' to 'Scaffolding' to Enhance Pre-Service Teachers' Critical Thinking - Ibrahim Ibrahim; Nurwahidah Nurwahidah; Ni Made Yeni Suranti; Nurkhaerat Alimuddin; Bahtiar Bahtiar; Maimun Maimun; Rangga Alif Faresta; Ismit Hi Karim; Trisno Setiawan (Balai Publikasi Indonesia, 2026)
This study addresses the